Prevalence of Salmonella spp. and Escherichia coli, in Rodents and Shrews with Their Associated Risk Factors - Marie Chantal Uwanyirigira; Elias Nelly Bapfakurera; Sarah Nibitangaza; Ginethon Gabriel Mhamphi; Elissa Mwega; Sharaduli Kimera; Abdul A.S Katakweba (Universitas Airlangga, 2024)
Background: Rodents are known to be a source of foodborne diseases; however, few researchers have examined rodent faeces. Purpose: This study aimed to determine the prevalence of foodborne Salmonella spp. and Escherichia coli (E. coli) and the risk factors associated with rodents and shrews in five wards from Morogoro Municipality, Tanzania. Method: A total of 148 rodents and shrews were captured from domestic, peri-domestic, and marketplace settings. This study isolated bacteria from faeces samples collected from rodents and shrews using a culture test, and identified them using biochemical tests. Molecular tests were used to screen out bacteria-targeted genes. Questionnaires were also used to assess the risk factors of foodborne Salmonella spp. and E. coli associated with house rodents and shrews. Results: Salmonella enterica was detected in 3/148 (2%), and E. coli was found in 54/148 (36.5%) of the samples. Regarding habitat, a high prevalence of E. coli was observed in open markets, at 16.9%, while Salmonella enterica was high inside households, at 1.3%. The results show that 83% of respondents found rodents feces in uncooked or cooked food, 30.4% found rodents feces in the water storage, 93.2% found food eaten by a rodent, and 66.9% of households used food contaminated with feces or eaten by rats. Conclusion: The study shows that rodents and shrews carry foodborne pathogens like Salmonella enterica and Escherichia coli in Morogoro municipality, Tanzania, posing serious public health risks. The rodents had high rates of E. coli and low Salmonella enterica, with risk factors linked to food and water contamination.